Recent Progress in 2D/3D Multidimensional Metal Halide Perovskites Solar Cells - Ge, Chuangye; Xue, Y.Z.B; Li, Liang; Tang, Bin; Hu, Hanlin (Frontiers in Materials, 2020)
The organic-inorganic hybrid perovskite solar cells with its great advances in the cost-efficient fabrication process and high-power conversion efficiency have outperformed a range of traditional photovoltaic technologies such as multi-crystal Si and CIGS. Meanwhile, the undesirable operational stability of perovskite solar cell lags its commercialization where perovskite solar cells suffer a lattice degradation and lost the capability of energy harvesting when encountering the crucial environmental factors such as high moisture and strong irradiation. Accordingly, improving the operational stability becomes one of the decisive factors to govern the next wave advancement of the perovskite solar cells. Among a plethora of reported strategies to improve the stability, building a multidimensional (2D/3D) heterojunction perovskite as the light-harvesting layer has recently become one of the most credible approaches to stabilize the PSCs without sacrificing of photovoltaic performance. In this mini-review, the recent progress in 2D/3D multidimensional PSCs has been elaborately reviewed. Detailed information including the long-chain cation materials, development of fabrication process, charge carrier dynamics, optoelectronic properties, and their impact on the photovoltaic performances has been systematically discussed. Finally, some of the further challenges are highlighted while outlining the perspectives of multidimensional 2D/3D perovskites for stable and high-performance PSCs.